Use of Human Granulocyte Colony-Stimulating Factor (G-CSF) in Consolidation Chemotherapy in Adult Acute Myeloid Leukaemia (AML) (Bangladesh Medical Journal, 2019)
Acute myeloid leukaemia (AML) is treatable and potentially curable disease. Significant morbidity is related to the prolonged, severe neutropenia resulting from the disease as well as the intensive chemotherapy. The administration of granulocyte - colony stimulating factor (G-CSF) is recommended to reduce the neutropenic period. But the current information and guidelines are insufficient about the most appropriate time to start   G-CSF and the optimum duration of treatment after chemotherapy in consolidation phase. This study explores  better timing to start G-CSF after completion of chemotherapy in consolidation phase of AML patient. This prospective study was conducted in the department of Haematology, Bangabandhu Sheikh Mujib Medical University among AML patients, who received consolidation chemotherapy (high dose cytarabine). Samples were grouped into two arms. Arm-A (Absolute Neutrophil Count >1000/cmm) received prophylactic G-CSF and Arm-B (Absolute Neutrophil Count